Vibration suppression of a tool in a lathe machine through contract-based design. Issue 5 (September 2016) - Awasthi, Aniket; Singh, Pushkar; Pujari, Prateek; Manupati, V.; Mahanty, B.; Tiwari, M.
Abstract Machine design is one of the most important tasks in the present scenario. Presently, machine design is done taking into account all the variables and operating conditions. The process is time consuming, error prone, and inefficient design methodology. Due to lack of optimization of the performance of individual components, the performance of the machine as a whole deteriorates. This paper aims at demonstrating the versatility of contract-based design methodology to design machines and overcome some of the drawbacks of the traditional designing process. The process variables involved in such a complex process are best modeled as fuzzy variables as they take non-discrete values. These fuzzy variables are analyzed using contract-based design. An illustration of lathe machine is used to enhance the machining capability by suppressing vibrations using a fuzzy controller and contract-based design. This leads to accurate machining with better tolerances and surface finish.